Low‐Temperature Sintering and Microwave Dielectric Properties of MgZrNb2O8 Ceramics with BaCu (B2O5) Addition. (31st December 2014) - Tang, Xin; Yang, Hui; Zhang, Qi‐long; Zhou, Jue‐hui
Abstract : The effects of BaCu (B2 O5 ) doping on sintering characteristics, phase constitute, and dielectric properties of MgZrNb2 O8 ceramics were investigated. Results indicated that a small amount of BaCu (B2 O5 ) can effectively lower the sintering temperature of MgZrNb2 O8 ceramics from 1300°C to 1100°C due to liquid phase sintering effect. However, the second phase of Ba3 Nb8 O21 appeared when the addition of BaCu (B2 O5 ) exceeds 2wt%. Typically, 2wt% BaCu (B2 O5 )‐added MgZrNb2 O8 ceramics sintered at 1100°C for 4 h could reach dense structure and exhibited microwave dielectric properties of ε r  = 25.96, Q×f =  65, 064GHz (f = 8.68GHz), and τ f   = −47 ppm/°C. Moreover, this ceramic has a chemical compatibility with Ag70/Pd30 electrodes, making it a very promising candidate material for the application of microwave multilayer electronic components.